Elimination of Aflatoxins from Two Selected Nigerian Vegetable Oils using Magnetic Chitosan Nanoparticles - Aringbangba, Oluyinka Eunice; Oluwafemi, Flora; Kolapo, Adelodun Lawrence; Adeogun, Abideen Idowu; Popoola, Temitope O. S. (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
Abstract Activated charcoal and imarsil (local adsorbent) had shown significant Aflatoxin (AF) decontamination potentials in vegetable oil at a low AF contamination level of ≤ 9 ng/L. AF contamination in vegetable oils can be more than a hundred-fold of this. Therefore, it is needed to investigate the potential of other adsorbents at higher AF contamination levels. Magnetic Chitosan Nanoparticle (MCNP) was synthesized, and its aflatoxins extraction efficiency from two edible vegetable oils was investigated. MCNP exhibited extraction efficiencies of 82.80 – 100% and 94.87 – 100% in palm kernel oil and palm oil at the contamination levels of 579.6 and 964.6 ng/L respectively. Total aflatoxins cleanup of the palm oil and palm kernel oil was possible at 30 °C within 30 and 60 minutes, respectively, at the optimized condition of 4.4 mg/L MCNP. MCNP concentration, temperature of extraction, and contact time were significant (p < 0.05) in palm kernel oil, while these conditions were not significant (p > 0.05) in palm oil. The results of the present investigation depict that the AF extraction efficiency of MCNP depends on the type of vegetable oil and that MCNP could be a credible alternative for AF decontamination of the investigated vegetable oil.Keywords: aflatoxins, chitosan, contamination, nanoparticles, vegetable oils AbstrakArang aktif dan imarsil (adsorben lokal) mempunyai potensi dekontaminasi aflatoksin (AF) yang signifikan dalam minyak nabati dengan tingkat kontaminasi AF rendah, yaitu ≤ 9 ng/L. AF dalam minyak nabati dapat lebih dari seratus kali lipat tingkat kontaminasi tersebut. Oleh karena itu, penelitian potensi adsorben lain perlu dilakukan pada tingkat kontaminasi AF yang lebih tinggi. Penelitian ini menganalisis sintesis Magnetic Chitosan Nanoparticle (MCNP) dan efisiensi ekstraksi aflatoksin dari dua minyak nabati konsumsi (minyak inti sawit dan minyak sawit). Efisiensi ekstraksi minyak inti sawit dan minyak sawit pada tingkat pencemaran 579,6 dan 964,6 ng/L, MCNP masing-masing sebesar 82,80 - 100% dan 94,87 - 100%. Pembersihan aflatoksin total pada minyak sawit dan minyak inti sawit dapat terjadi pada suhu 30 °C dalam waktu masing-masing 30 dan 60 menit, pada kondisi optimal MCNP, yaitu 4,4 mg/L. Konsentrasi MCNP, suhu ekstraksi, dan waktu kontak signifikan (p < 0,05) pada minyak inti sawit, tetapi kondisi ini tidak signifikan (p > 0,05) pada minyak kelapa sawit. Hasil penelitian ini menunjukkan bahwa efisiensi ekstraksi AF MCNP tergantung pada jenis minyak nabati dan MCNP dapat menjadi alternatif untuk dekontaminasi AF dari minyak nabati yang diteliti.Kata kunci: aflatoksin, kitosan, kontaminasi, minyak nabati, nano partikel